Case-Mix Accounting System Design in Social and Health Care Sector - The Mechanisms of Hybridization - Henri Teittinen; Janina Männikkö (European Financial and Accounting Journal, 2022)
The purpose of this paper is to explore the design process of a case-mix accounting system. Particularly, we focus on hybridization, highlighting how nonfinancial staff became involved and interested in case-mix accounting. This study is a qualitative case study, illustrating the case-mix accounting system design in one case organization. We identified authority, competence, rhetorical, and scoring mechanisms. The authority mechanism provides the basis for the design of the case-mix accounting system; the competence mechanism supports the ability of personnel to participate in service design; the rhetorical mechanism makes things more vernacular; and the scoring mechanism defines and categorizes but also supports management control. Our results support also practical implications in management control in the social and health care sector.
Keywords: M41; 650; Case-Mix Accounting; Hybridization; Social and Health Care Sector